Aspen mortality in the Colorado and southern Wyoming Rocky Mountains: extent, severity, and causal factors - Dudley, Megan, author; Jacobi, William R., advisor; Tisserat, Ned A., committee member; Negron, Jose, committee member; Martin, Patrick H., committee member (Colorado State University. Libraries, 2011)
Quaking aspen (Populus tremuloides Michx) is a deciduous hardwood tree widely distributed throughout North America. In Colorado, quaking aspen is found on a wide variety of sites, from the lower-elevation foothills of the eastern edge of the Rockies to moderate- and high- elevation montane sites throughout the Rocky Mountains. Aspen dieback has been documented throughout western North America over the past decade, resulting in stands that have either elevated proportions of overstory mortality or thin crowns, or both. Stands experiencing dieback may or may not produce regeneration cohorts. In this study, we surveyed aspen in the north-western corner of Colorado on the White River and Routt national forests, along the front range of Colorado on the Pike-San Isabel national forests, and in the south-central region of Wyoming on the Medicine Bow national forest during 2009 - 2010. We established 573 random roadside survey plots in stands that contained at least 50% aspen cover type. From these random plots, we found average standing aspen tree mortality ranged from 3.3 to 23.7 % on the four national forests and 11% on the east side of the continental divide and 4 % on the west side. The roadside plot data suggests that Colorado's aspen on these four national forests overall were healthy; mortality rates among aspen were fairly low (~3 - 8%) among all stems, and average percent live crown among adults was high (~85 - 90%), in spite of nearly ubiquitous presence of disease (~97 - 99%) and high incidence of insect damage (~50 - 75%). We also established 98 aspen stand assessment plots with half of the plots in damaged stands, as defined by U.S.D.A. Forest Service aerial detection surveys (ADS), and half in healthy aspen stands. Damaged stands were defined as those stands with (1) thinning crowns among at least 25% of adult aspen, (2) stands with moderate (<50% of stems) levels of overstory mortality, or (3) stands with high (>50% of stems) levels of overstory mortality. Healthy aspen stands were defined as having (1) a maximum mortality rate of 5 - 7% among all aspen, and/or (2) more than 75% of adult aspen with full crowns. Adult aspen in damaged stands tended to be less vigorous, based a health score index from 1 to 5, with higher scores indicating less healthy conditions (where 1=0-25% damage; 2 = 25-50% damage; 3 = >50% damage; 4 = recent dead; 5 = >5 years dead). Health scores averaged 1.7 in healthy stands, compared to 2.3 in damaged stands. Saplings in damaged stands tended to be healthier with a score of 1.7, compared to 2.2 in healthy stands. Further, there was no difference in the proportion live or total numbers of saplings per hectare between healthy and damaged stands. The prevalence of damaging organisms, such as Cytospora canker (20% in damaged, 13% in healthy), wood-boring insects (27% in damaged, 10% in healthy), and aspen bark beetles (16% in damaged, 7% in healthy) was considerably greater among damaged stands. Site conditions also influenced the prevalence of some of these damage agents: bark beetles were most common among stands at low elevations (18%, compared to 11% and 6% at moderate and high elevations, respectively); Cytospora canker was most common among stands on south- or west-facing aspects (20% and 19%, respectively); both aspen bark beetles and Cytospora canker were also most common among stands in the southernmost section of the survey area, the Pike-San Isabel national forest (41% and 36%). There was no difference in the severity of canker or decay fungal infection between healthy and damaged stands. Cytospora canker infestations were more severe on the Medicine Bow NF compared to the other three national forests, and Marssonina foliar blight infection appeared to be most severe on slope summits, concave sites, and sites with either no to low percent slope or moderately steep slopes. Based on the general state of aspen health within the study area, it appears that aspen in damaged stands were experiencing more severe environmental stress (e.g., late frost, drought, defoliation) and coupled with disease and insect infestations, resulted in greater mortality when compared to healthy stands. The severity of such conditions appears to be regional in scale, and it remains to be established that long-term or acute drought is the major factor influencing the observed conditions. Since no differences were detected in regeneration density between damaged or non-damaged stands, it is possible that there will be no long-lasting effects on aspen longevity on these sites with the relatively low incidence of overstory mortality throughout all four national forests.
Keywords: aspen; decline; dieback; disturbance; SAD; Populus tremuloides